Insurance coverage and respiratory morbidities in bronchopulmonary dysplasia. Issue 7 (26th April 2022) - Collaco, Joseph M.; Tracy, Michael C.; Sheils, Catherine A.; Rice, Jessica L.; Rhein, Lawrence M.; Nelin, Leif D.; Moore, Paul E.; Manimtim, Winston M.; Levin, Jonathan C.; Lai, Khanh; Hayden, Lystra P.; Fierro, Julie L.; et al.
Abstract: Introduction: Preterm infants and young children with bronchopulmonary dysplasia (BPD) are at increased risk for acute care utilization and chronic respiratory symptoms during early life. Identifying risk factors for respiratory morbidities in the outpatient setting could decrease the burden of care. We hypothesized that public insurance coverage was associated with higher acute care usage and respiratory symptoms in preterm infants and children with BPD after initial neonatal intensive care unit (NICU) discharge. Methods: Subjects were recruited from BPD clinics at 10 tertiary care centers in the United States between 2018 and 2021. Demographics and clinical characteristics were obtained through chart review. Surveys for clinical outcomes were administered to caregivers. Results: Of the 470 subjects included in this study, 249 (53.0%) received employer‐based insurance coverage and 221 (47.0%) received Medicaid as sole coverage at least once between 0 and 3 years of age. The Medicaid group was twice as likely to have sick visits (adjusted odd ratio [OR]: 2.06; p  = 0.009) and emergency department visits (aOR: 2.09; p  = 0.028), and three times more likely to be admitted for respiratory reasons (aOR: 3.04; p  = 0.001) than those in the employer‐based group. Additionally, those in the Medicaid group were more likely to have nighttime respiratory symptoms (aOR: 2.62; p  = 0.004). Conclusions: Children with BPD who received Medicaid coverage were more likely to utilize acute care and have nighttime respiratory symptoms during the first 3 years of life. More comprehensive studies are needed to determine whether the use of Medicaid represents a barrier to accessing care, lower socioeconomic status, and/or a proxy for detrimental environmental exposures.